Characteristics and fabrication of nanohole array on InP semiconductor substrate using nanoporous alumina - Jung, Mi; Lee, Seok; Byun, Young Tae; Jhon, Young Min; Kim, Sun Ho; Woo, Deok-Ha; Mho, Sun-il (ELSEVIER SCI LTD, 2008)
Uniform arrays of nano-sized pore produced in porous alumina were transferred into InP substrates by inductively coupled plasma reactive ion etching (ICP-RIE). We observed a significant enhancement in the light output from InP substrate with nanohole arrays on the surface. Photoluminescence intensity of triangular arrays of air cylinders on InP substrate showed an enhancement up to 3 times compared with that from a raw InP substrate without such structure. The ICP-RIE technique using nanoporous alumina mask can be used as a prospective method in the fabrication of nanostructure materials for increasing the light output from semiconductor light emitting devices. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: ANODIC ALUMINA; POROUS ALUMINA; TEMPLATES; GAAS; MASK